D-Cycloserine enhances durability of social skills training in autism spectrum disorder. Issue 1 (December 2017) - Wink, Logan; Minshawi, Noha; Shaffer, Rebecca; Plawecki, Martin; Posey, David; Horn, Paul; Adams, Ryan; Pedapati, Ernest; Schaefer, Tori; McDougle, Christopher; Swiezy, Naomi; Erickson, Craig
Abstract Background d -Cycloserine (DCS) enhances extinction learning across species, but it has proven challenging to identify consistent benefit of DCS when added to therapeutic interventions. We conducted a placebo-controlled trial of DCS to potentiate social skills training in autism spectrum disorder (ASD) but found substantial improvement in both the DCS and placebo groups at the conclusion of active treatment. Here, we assess the impact of DCS 11 weeks following active treatment to evaluate the impact of DCS on treatment response durability. Methods Study participants included 60 outpatient youth with ASD, ages 5–11 years, all with IQ above 70, and significantly impaired social functioning who completed a 10-week active treatment phase during which they received weekly single doses of 50 mg of DCS or placebo administered 30 min prior to group social skills training. Following the 10-week active treatment phase, blinded follow-up assessments occurred at week 11 and week 22. The primary outcome measure for our durability of treatment evaluation was the parent-rated social responsiveness scale (SRS) total raw score at week 22. Results Analysis of the SRS total raw score demonstrated significant decrease for the DCS group compared to the placebo group (p = 0.042) indicating greater maintenance of treatment effect in the DCS group. DCS was well tolerated, with irritability being the most frequently reported adverse effect in both groups. Conclusions The findings of this study suggest that DCS may help youth with ASD to maintain skills gained during sort-term social skills training. Larger-scale studies with longer follow-up will be necessary to further understand the long-term impact of DCS paired with structured social skills training. Trial registration ClinicalTrials.gov, NCT01086475